Art Education and Design Thinking: Reflections on Students Engaging With Community Using Design - Wiebe, Michelle; Seaton, Sheilagh (Canadian Review of Art Education / Revue canadienne d'éducation artistique, 2021)
The creative process has long been interwoven with art education practice. Design thinking has numerous parallels to the creative process and may be viewed as an appropriate method to encourage creative thinking in both art and design students. This observational case study reflects on two disparate challenges in which 47 students tackled aesthetic and community provocations by applying the design thinking process. Reflective consideration of the results of each ‘project’ provides insight into the application and value of a proposed Design Thinking framework in art and design education.